Deadly income inequality? a panel data analysis on the impact of income inequality on mental disorder mortality - Goh, Lim Thye (Universiti Malaysia Sarawak, 2022)
This study investigated the impact of income inequality on mental disorder mortality. The present study also sought to discover the role of institutional quality in moderating the income inequality-mental disorder mortality nexus. The analysis used panel system generalized method of moments (GMM) estimations on data from developed and developing countries from 1989 to 2018. The analysis findings indicated that income inequality positively impacted mental disorder mortality in the total sample and developed countries but was insignificant for developing countries. In addition, the income-inequality-mental disorder mortality nexus was contingent on institutional quality, indicating that better institutional quality could alleviate the effect of income inequality on mental health, especially in developed countries. © 2022, Universiti Malaysia Sarawak. All rights reserved.